THE INFLUENCE OF PRICE AND ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASE DECISIONS ON TIKTOKSHOP - Emi Amelia; Ratih Hurriyati; Mokh. Adib Sultan; Heny Hendrayanti; Christianingrum Christianingrum (JURNAL BISNIS STRATEGI, 2022)
E-commerce is a successful business model today. Tiktok Shop, a new platform launched by the social media platform TikTok, quickly became a popular trading platform, making Tiktokshop a social trading platform. The purpose of this study was conducted to find out the description of consumer purchasing decisions, prices, electronic word of mouth (E-WOM) on Tiktokshop. The type of research used was descriptive verification, and the method used was an explanatory survey with a purposive sampling technique with a sample size of 100 respondents. The data analysis method used is the validity and reliability test, multiple regression analysis, multiple correlation analysis and analysis of the coefficient of determination. Testing this hypothesis through the F test for simultaneous and T test for partial by using the SPSS 22.0 for windows program. The results showed that simultaneously price, electronic word of mouth (E-WOM) had a significant effect on purchasing decisions by 72.8%.